U1 Small Nuclear Ribonucleoprotein and Splicing Inhibition by the Rous Sarcoma Virus Negative Regulator of Splicing Element - McNally, Lisa M. (American Society for Microbiology, 1999)
Retroviruses require both spliced and unspliced RNA for replication. Accumulation of unspliced Rous sarcoma virus RNA is facilitated in part by a negative cis element in the gag region, termed the negative regulator of splicing (NRS), which serves to repress splicing of viral RNA but can also block splicing of heterologous introns. The NRS binds components of the splicing machinery including SR proteins, U1 and U2, small nuclear ribonucleoproteins (snRNPs) of the major splicing pathway, and U11 snRNP of the minor pathway, yet splicing does not normally occur from the NRS. A mutation that abolishes U11 binding (RG11) also abrogates NRS splicing inhibition, indicating that U11 is functionally important for NRS activity and suggesting that the NRS is recognized as a minor-class 5′ splice site (5′ ss). We show here, using specific NRS mutations to disrupt U11 binding and coexpression of U11 snRNA genes harboring compensatory mutations, that the NRS U11 site is functional when paired with a minor-class 3′ ss from the human P120 gene. Surprisingly, the expectation that the same NRS mutants would be defective for splicing inhibition proved false; splicing inhibition was as good as, if not better than, that for the wild-type NRS. Comparison of these new mutations with RG11 indicated that the latter may disrupt binding of a factor(s) other than U11. Our data suggest that this factor is U1 snRNP and that a U1 binding site that overlaps the U11 site is also disrupted by RG11. Analysis of mutations which selectively disrupted U1 or U11 binding indicated that splicing inhibition by the NRS correlates most strongly with U1 snRNP. Additionally, we show that U1 binding is facilitated by SR proteins that bind to the 5′ half of the NRS, confirming an earlier proposal that this region is involved in recruiting snRNPs to the NRS. These data indicate a functional role for U1 in NRS-mediated splicing inhibition.